Preparation and Bioactivity Properties of a Novel Composite Membrane of Fructose Mediated β-Tricalcium Pyrophosphate/(Polyethylene Glycol/Chitosan) for Guided Tissue Regeneration - Jian-Wen Wang; Min-Hsiung Hon; Yi-Ming Kuo; Mei-Hui Chung (International Journal of Polymer Science)
A novel composite membrane of β-tricalcium pyrophosphate (β-TCP) and fructose- (F-) mediated chitosan/poly(ethylene glycol) (CS/PEG) was prepared by thermally induced phase separation technique. The prepared composite membranes were characterized using scanning electron microscopy (SEM) and X-ray diffraction (XRD). The mechanical property, swelling, degradation, and cytotoxicity of the composite membranes were evaluated in vitro with respect to its potential for use as biodegradable guided tissue regeneration (GTR) membrane. In vitro degradation tests showed the composite membrane with a controllable degradation rate when changing the β-TCP content. The incorporation of β-TCP granules also caused a significant enhancement of tensile strength. When β-TCP content is controlled to 50 wt%, homogeneous composite membranes with well mechanical property and enzymatic degradation rate can be obtained. Cytotoxicity assay demonstrates that the composite membranes were nontoxic and had very good cell compatibility. Most importantly, the release of calcium ions and glucosamine from the composite membranes was proved to increase the cell proliferation of NIH3T3. The results of this study have indicated that this novel F-β-TCP/CS/PEG composite can be a suitable material for GTR applications.